Partial purification of the Pasteurella multocida toxin from serotype A: 12 of goat - SUNDER, JAI; KUMAR, A A (The Indian Journal of Animal Sciences, 2013)
In this study.a partial purificaation of the Pasteurella multocida toxin (PMT) from serotype A: 12 of goat origin was carned out and Its biological activities were assessed. The crude toxin (the sonicated filtered supernatant) was passed through DEAE-sephacel anion exchanger column and then filtered though sepbadex. G-200 co1umn. At every steps SDS-PAGE was done to check the purity of the toxin. The result showed that the minimal dermonecrotic dose in guineapigs vaned from 1.4-4.6 ug and minimal lethal dose in mice varied from 2.1 to 6.9 ug of the partially purified PMT. The specific activity of the partially purified PMT increased by 200-fold and the average yield of the partially purified PMT was about 10%. The molecular weight of the partially purified PMT was 72.0 kDa. Six major and 3 minor immunodorninant proteins were obtained by immunoblotting.